Il Secolo Illustrato - Unknown (Massachusetts Institute of Technology. Libraries. Department of Distinctive Collections, 1892)
Clipping from the Italian newspaper "Il Secolo Illustrato" containing an article about traveling to the North Pole by balloon (page 366). For more information about this item, visit https://archivesspace.mit.edu/repositories/2/digital_objects/814